Assessment of stability of sulphated lactosyl archaeol archaeosomes for use as a vaccine adjuvant. (3rd July 2021) - Jia, Yimei; Chandan, Vandana; Akache, Bassel; Qian, Hui; Jakubek, Zygmunt J.; Vinogradov, Evguenii; Dudani, Renu; Harrison, Blair A.; Jamshidi, Mohammad P.; Stark, Felicity C.; Deschatelets, Lise; Sauvageau, Janelle; et al.
Abstract: Archaeosomes, composed of sulphated lactosyl archaeol (SLA) glycolipids, have been proven to be an effective vaccine adjuvant in multiple preclinical models of infectious disease or cancer. In addition to efficacy, the stability of vaccine components including the adjuvant is an important parameter to consider when developing novel vaccine formulations. To properly evaluate the potential of SLA glycolipids to be used as vaccine adjuvants in a clinical setting, a comprehensive evaluation of their stability is required. Herein, we evaluated the long term stability of preformed empty SLA archaeosomes prior to admixing with antigen at 4 °C or 37 °C for up to 6 months. In addition, the stability of adjuvant and antigen was evaluated for up to 1 month following admixing. Multiple analytical parameters evaluating the molecular integrity of SLA and the liposomal profile were assessed. Following incubation at 4 °C or 37 °C, the SLA glycolipid did not show any pattern of degradation as determined by mass spectroscopy, nuclear magnetic resonance (NMR) and thin layer chromatography (TLC). In addition, SLA archaeosome vesicle characteristics, such as size, zeta potential, membrane fluidity and vesicular morphology, were largely consistent throughout the course of the study. Importantly, following storage for 6 months at both 4 °C and 37 °C, the adjuvant properties of empty SLA archaeosomes were unchanged, and following admixing with antigen, the immunogenicity of the vaccine formulations was also unchanged when stored at both 4 °C and 37 °C for up to 1 month. Overall this indicates that SLA archaeosomes are highly stable adjuvants that retain their activity over an extended period of time even when stored at high temperatures.